STRATEGI BERTAHAN DAN MELAWAN: UPAYA MASYARAKAT HULU KUANTAN DALAM MENGHADAPI TENTARA JEPANG DAN BELANDA (1942-1949) - Amanan Amanan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study examines the strategies of rural communities in responding to wartime violence during the period 1942–1949 in Kuantan Hulu, highlighting the transformation of responses from the Japanese occupation to the Indonesian Revolution. This research employs the historical method, including heuristics, source criticism, interpretation, and historiography. It also adopts an oral history approach by conducting interviews with local communities. In addition, the study utilizes material evidence in the form of protective shelters to visualize the memory of the community regarding the revolutionary period.The findings show that during the Japanese occupation, although communities lived under pressure, they still had room to carry out covert resistance, one of which was by deceiving Japanese soldiers through the use of local knowledge of river environments. Meanwhile, during the Indonesian Revolution, the increasing intensity of violence through Dutch military operations limited the possibility of resistance, leading communities to shift toward survival strategies by constructing protective underground shelters around their homes.This transformation indicates that community responses to war were adaptive and situational. The study emphasizes that civilians were not merely passive victims, but also active agents who exercised agency in determining their survival strategies. Furthermore, this research contributes to enriching the understanding of community experiences during wartime in Indonesia. Keywords: Kuantan, Revolution, Japanese Occupation, Resistence.